Pengelolaan dan Pelaporan Konvergensi Pencegahan Bahaya Stunting Desa Dilayah Kecamatan Kabupaten Banyumas - ABDUL AZIS (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
One of the requirements for the distribution of village funds for the third phase is the results of the report on the convergence of stunting prevention at the village level for the previous fiscal year. The process of managing and reporting stunting prevention convergence data at the village level in the Kembaran District, Banyumas Regency is still carried out by means of written records which are then transferred into Microsoft Excel form. Constraints faced are the length of the recapitulation process and the preparation of a convergence report on stunting prevention because they have to work twice and have to manually adjust the number of service acceptance statuses. The purpose of this research is to produce an e-Stunting application, which is a website-based application for managing and reporting the convergence of stunting prevention. Researchers in data collection using observation techniques, interviews, documentation, and literature study. The method for application development uses the Extreme Programming (XP) method. This research has succeeded in creating an e-Stunting application that can recapitulate and generate reports of stunting convergence automatically.